Ambroxol Treatment Suppresses the Proliferation of Chlamydia pneumoniae in Murine Lungs - Kókai, Dávid (Microorganisms, 2021)
Ambroxol (Ax) is used as a mucolytics in the treatment of respiratory tract infections. Ax, at a general dose for humans, does not alter Chlamydia pneumoniae growth in mice. Therefore, we aimed to investigate the potential anti-chlamydial effect of Ax at a concentration four timed higher than that used in human medicine. Mice were infected with C. pneumoniae and 5-mg/kg Ax was administered orally. The number of recoverable C. pneumoniae inclusion-forming units (IFUs) in Ax-treated mice was significantly lower than that in untreated mice. mRNA expression levels of several cytokines, including interleukin 12 (IL-12), IL-23, IL-17F, interferon gamma (IFN-γ), and surfactant protein (SP)-A, increased in infected mice treated with Ax. The IFN-γ protein expression levels were also significantly higher in infected and Ax-treated mice. Furthermore, the in vitro results suggested that the ERK 1/2 activity was decreased, which is essential for the C. pneumoniae replication. SP-A and SP-D treatments significantly decreased the number of viable C. pneumoniae IFUs and significantly increased the attachment of C. pneumoniae to macrophage cells. Based on our results, a dose of 5 mg/kg of Ax exhibited an anti-chlamydial effect in mice, probably an immunomodulating effect, and may be used as supporting drug in respiratory infections caused by C. pneumoniae.